Assessing skeletal muscle mass: historical overview and state of the art. Issue 1 (15th February 2014) - Heymsfield, Steven B.; Adamek, Michael; Gonzalez, M. Cristina; Jia, Guang; Thomas, Diana M.
Abstract : Background: Even though skeletal muscle (SM) is the largest body compartment in most adults and a key phenotypic marker of sarcopenia and cachexia, SM mass was until recently difficult and often impractical to quantify in vivo. This review traces the historical development of SM mass measurement methods and their evolution to advances that now promise to provide in‐depth noninvasive measures of SM composition. Methods: Key steps in the advancement of SM measurement methods and their application were obtained from historical records and widely cited publications over the past two centuries. Recent advances were established by collecting information on notable studies presented at scientific meetings and their related publications. Results: The year 1835 marks the discovery of creatine in meat by Chevreul, a finding that still resonates today in the D3 ‐creatine method of measuring SM mass. Matiegka introduced an anthropometric approach for estimating SM mass in 1921 with the vision of creating a human "capacity" marker. The 1940s saw technological advances eventually leading up to the development of ultrasound and bioimpedance analysis methods of quantifying SM mass in vivo. Continuing to seek an elusive SM mass "reference" method, Burkinshaw and Cohn introduced the whole‐body counting‐neutron activation analysis method and provided some of the first detailed reports of cancer cachexia in the late 1970s. Three transformative breakthroughs leading to the current SM mass reference methods appeared in the 1970s and early 1980s as follows: the introduction of computed tomography (CT), photon absorptiometry, and magnetic resonance (MR) imaging. Each is advanced as an accurate and/or practical approach to quantifying whole‐body and regional SM mass across the lifespan. These advances have led to a new understanding of fundamental body size‐SM mass relationships that are now widely applied in the evaluation and monitoring of patients with sarcopenia and cachexia. An intermediate link between SM mass and function is SM composition. Advances in water‐fat MR imaging, diffusion tensor imaging, MR elastography, imaging of connective tissue structures by ultra‐short echo time MR, and other new MR approaches promise to close the gap that now exists between SM anatomy and function. Conclusions: The global efforts of scientists over the past two centuries provides us with highly accurate means by which to measure SM mass across the lifespan with new advances promising to extend these efforts to noninvasive methods for quantifying SM composition.